Who Fights Terror: Gendarmerie Forces and Terrorist Group Termination - Kirisci, Mustafa (Terrorism and political violence, 2022)
While existing research on terrorist group termination examines numerous factors explaining why some terror groups end their campaigns of violence, these studies do not sufficiently address the impact that the actors who actively fight these groups have on the probability of a group’s demise. This paper explores the effect of gendarmeries on terrorist group termination. Gendarmeries may either contribute positively to the counterterrorism efforts of the state with their policing and military operations, or they may undermine these efforts to the extent that they become unaccountable to the state for their actions. Lax accountability may lead to principle-agent problems, resulting in an increase in the risk of those groups engaging in repressive or rent-seeking actions, which can undermine support for the government and contribute to the survival of the terror group. It is argued that the competing ways in which gendarmeries can affect counterterrorism efforts are conditioned by the bureaucratic effectiveness of the state in managing the activities of gendarmerie forces and by the state’s commitment to upholding the rule of law. The results of empirical analyses reveal that having gendarmeries increases a terrorist group’s chance of ending their campaign of violence but decreases the likelihood of a group’s demise in states marked by lower bureaucratic effectiveness and weak rule of law.